Pessary use in patients diagnosed with short cervix and cervical insufficiency. (19th May 2022) - Herkiloglu, Dilsad; Ayvacı, Habibe; Pekin, Oya; Tarhan, Nazan; Karateke, Ateş; Sahin, Sadik
Abstract: Objective: The aim was to evaluate the effectiveness of Arabin pessary use in patients with cervical insufficiency or short cervix before the 24th week of gestation and the impact of cervical examination findings prior to pessary application on the outcome in terms of the gestational week. Materials and methods: In our study, among the pregnancies between the 12th and 24th gestational weeks, 60 pregnant women with a preterm delivery history and/or cervical length less than 25 mm were included. Among these 60 patients, 43 of them had a short cervix, 17 of them had cervical insufficiency. Routine medical and obstetric history was obtained. In the vaginal examination, the cervix was evaluated in terms of patency, dilatation, and position. Cervical length, presence of debris, and funneling were evaluated by transvaginal ultrasound. After receiving patients' approval a cervical pessary was applied to patients. Pessaries of pregnant women with 37 weeks of gestation were removed. Before reaching the 37th gestation week, pessaries were withdrawn in patients who had ongoing vaginal bleeding, premature rupture of membranes, and preterm contractions unresponsive to tocolytic treatment. Results: Thirty-one pregnant women (51.7%) out of 60 pregnant women who underwent pessary, delivered at 37 weeks and below. Delivery rates in the short cervical measurement group and cervical insufficiency group at ≤28 weeks, ≤34 weeks and ≤37 weeks were respectively ( n = 21) 34.8% vs 36.3% ( p = 0.976), ( n = 29) 41.8% vs 64.7% ( p = 0.111), ( n = 31) 44.2% vs 70.6% ( p = 0.888). The presence of cervical funneling before pessary application shows a statistically significant difference in terms of patient's giving birth before or after 28 weeks ( p = 0.033). In patients with cervical funneling, there was a significant increase in a birth before 28 weeks. Depending on whether or not patients applying with pain need for tocolysis, it shows the statistically meaningful difference in terms of the patients giving birth before or after 34 weeks ( p = 0.001) (OR 7, 61, 95% GA 2.4–24.6). In the group without the need for tocolysis, there is a meaningful increase in birth after 34 weeks. Conclusions: Our findings showed that, alongside the defined cervical risk factors, cervical funneling and the need for tocolysis are remarkable prognostic variables in pessary application.